2023
DOI: 10.1111/pai.13911
|View full text |Cite
|
Sign up to set email alerts
|

Expected impact of immunomodulatory agents during pregnancy: A newborn's perspective

Abstract: The neonatal immune ontogeny begins during pregnancy to ensure that the neonate is well-suited for perinatal life. It prioritizes Th2/M2 and regulatory responses over Th/M1 activity to avoid excessive inflammatory responses and to ensure immune tolerance and homeostasis. Newborns also present increased Th17/Th22 responses providing effective anti-fungal immunity and mucosal protection. Intrauterine exposure to immune modulatory drugs with the placental transfer may influence the natural course of the fetal imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 77 publications
(162 reference statements)
1
1
0
Order By: Relevance
“…Concerning the Eo/Bas cluster, we observed a high and exclusive expression of anti-inflammatory cytokines Il4 and Il13 . In line with our observations, basophil cells in newborns were shown to skew the differentiation of T cells towards Th2, which in newborns have an anti-inflammatory profile to protect intestinal microbiota and prevent tissue damage (Dhakal et al, 2015; Luo et al, 2023). Highlighting the predicted interdependency between compartments, both hematopoietic clusters also express key factors mediating bone healing ( Ccl5 (Ortinau et al, 2019) in ILC-TSP2) and osteogenesis-adipogenesis balance ( Osm (Li et al, 2022a) in Eo/Bas).…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the Eo/Bas cluster, we observed a high and exclusive expression of anti-inflammatory cytokines Il4 and Il13 . In line with our observations, basophil cells in newborns were shown to skew the differentiation of T cells towards Th2, which in newborns have an anti-inflammatory profile to protect intestinal microbiota and prevent tissue damage (Dhakal et al, 2015; Luo et al, 2023). Highlighting the predicted interdependency between compartments, both hematopoietic clusters also express key factors mediating bone healing ( Ccl5 (Ortinau et al, 2019) in ILC-TSP2) and osteogenesis-adipogenesis balance ( Osm (Li et al, 2022a) in Eo/Bas).…”
Section: Discussionsupporting
confidence: 89%
“…The use of immunomodulators during pregnancy has gained global interest. Current evidence mainly reports outcomes related to the newborn and the potential effect on the ontogeny of the immune system [56]. Previous studies have reported the effects of cytokines [21,57] as immunomodulators capable of acting on blood viscosity.…”
Section: Discussionmentioning
confidence: 99%